Preferences of People of Advanced and Gerontic Age in Diet Formation - Ruban N.; Reznichenko I. (Техника и технология пищевых производств)
Introduction. Currently, the food market is replenished with new types of specialized food products intended for nutrition of certain population categories. Gerodietetic products are important in forming the diet for senior citizens. Therefore, gerodietetic foods are a factor of healthy lifestyle and active longevity. Functional food products should be based on age-related issues and consumer preferences. Aging weakens assimilative processes in organs and tissues, slows down the rate of redox reactions, and restructures the system of metabolism and body functions. Thus, people of advanced and gerontic age need to consume appropriate amount of vitamins and minerals, as their deficiency plays a decisive role in the development of age-related diseases. As a result, scientific justification and development of functional food products for this category is extremely important. The research objective was to study consumer preferences in relation to gerodietetic food products by collecting, processing, and analyzing marketing data. Study objects and methods. The research featured statistical data, as well as information obtained from consumers aged 60–77, residents of the Kemerovo region. The study involved methods of analysis, systematization of statistical and scientific information, comparison and generalization, as well as a marketing survey method. Results and discussion. The research started with an analysis of the structure and dynamics of the age-sex composition of the population in 2017–2019. The number of the elderly increased by 5% compared to 2017. The analysis also showed a stable quantitative prevalence of female population, i.e. 64.9% in 2017 and 64.8% in 2019. The daily diet of most survey participants included cereals, dairy products, and vegetables. The survey helped to identify the purchase factors. Price proved to be the main factor when choosing dairy products (72%). Most respondents (47%) consume dairy products daily. Conclusion. The marketing research defined the purchase factors for people of advanced and gerontic age in choosing food products. The obtained data can help to improve the gerodietetic products on the consumer market of Kemerovo.